2015
DOI: 10.1111/vcp.12266
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N‐terminal pro‐B‐type natriuretic peptide concentration in healthy retired racing Greyhounds

Abstract: Plasma NT-proBNP concentration in Greyhounds is high and should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Although the healthy cats were from 3 genetically distant breeds, 38 with >30 cats/breed (see Table 2), no significant difference in NT‐proBNP concentration was found among the breeds, which is in accordance with a previous study that included several different breeds with variable and often small breed group sizes 14 . This finding is in contrast to studies in dogs, in which significant interbreed differences have been found in NT‐proBNP concentrations 19,39 …”
Section: Discussionsupporting
confidence: 87%
“…Although the healthy cats were from 3 genetically distant breeds, 38 with >30 cats/breed (see Table 2), no significant difference in NT‐proBNP concentration was found among the breeds, which is in accordance with a previous study that included several different breeds with variable and often small breed group sizes 14 . This finding is in contrast to studies in dogs, in which significant interbreed differences have been found in NT‐proBNP concentrations 19,39 …”
Section: Discussionsupporting
confidence: 87%
“…Several physiological and pathological factors can influence the reported concentrations of both NT‐proBNP and cTnI, potentially confounding the associations between the biomarkers and survival . Breed, sex, body weight, age, treatments, and comorbidities were evaluated both as explanatory variables and confounders in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in retired racing greyhounds have found that plasma NT-proBNP concentrations in this breed at rest are significantly higher than non-Greyhound controls, with 11 of 24 healthy greyhounds having NT-proBNP concentrations above the upper limit of the reference range. 35 A similar situation might exist in Huntaways, and there might also be an influence of sex on plasma NT-proBNP concentrations at rest, although in humans, females tend to have higher concentrations than males. 36 The high before work NT-proBNP concentrations on Day 1 could also be related to the dogs' anticipation of imminent work after a fortnight of rest.…”
Section: Discussionmentioning
confidence: 84%
“…Because of the small sample size in the present study, it might be coincidental that the 2 dogs with elevated NT‐proBNP concentrations initially were both male Huntaways, whereas the 2 female Huntaways and the heading dogs had resting values within the reference range. However, studies in retired racing greyhounds have found that plasma NT‐proBNP concentrations in this breed at rest are significantly higher than non‐Greyhound controls, with 11 of 24 healthy greyhounds having NT‐proBNP concentrations above the upper limit of the reference range . A similar situation might exist in Huntaways, and there might also be an influence of sex on plasma NT‐proBNP concentrations at rest, although in humans, females tend to have higher concentrations than males .…”
Section: Discussionmentioning
confidence: 86%